Neurobiological effect of selective brain cooling after concussive injury. - Walter, Alexa; Finelli, Katie; Bai, Xiaoxiao; Johnson, Brian; Neuberger, Thomas; Seidenberg, Peter; Bream, Timothy; Hallett, Mark; Slobounov, Semyon (Brain Imaging & Behavior, 2018)
The search for effective treatment facilitating recovery from concussive injury, as well as reducing risk for recurrent concussion is an ongoing challenge. This study aimed to determine: a) feasibility of selective brain cooling to facilitate clinical symptoms resolution, and b) biological functions of the brain within athletes in acute phase of sports-related concussion. Selective brain cooling for 30 minutes using WElkins sideline cooling system was administered to student-athletes suffering concussive injury (n=12; tested within 5±3 days) and those without history of concussion (n=12). fMRI and ASL sequences were obtained before and immediately after cooling to better understanding the mechanism by which cooling affects neurovascular coupling. Concussed subjects self-reported temporary relief from physical symptoms after cooling. There were no differences in the number or strength of functional connections within Default Mode Network (DMN) between groups prior to cooling. However, we observed a reduction in the strength and number of connections of the DMN with other ROIs in both groups after cooling. Unexpectedly, we observed a significant increase in cerebral blood flow (CBF) assessed by ASL after selective cooling in the concussed subjects compared to the normal controls. We suggest that compromised neurovascular coupling in acute phase of injury may be temporarily restored by cooling to match CBF with surges in the metabolic demands of the brain. Upon further validation, selective brain cooling could be a potential clinical tool in the minimization of symptoms and pathological changes after concussion.